Noninferiority of local control and comparable toxicity of intensity modulated radiation therapy with simultaneous integrated boost in breast cancer: 5-year results of the IMRT-MC2 phase III trial - Forster, Tobias; Köhler, Clara; Dorn, Melissa; Häfner, Matthias; Arians, Nathalie; König, Laila; Harrabi, Semi B.; Schlampp, Ingmar; Weykamp, Fabian; Meixner, Eva; Uzun-Lang, Kristin; Heinrich, Vanessa; et al. (International journal of radiation oncology, biology, physics, 2023)
Purpose - The IMRT-MC2 trial was conducted to demonstrate the noninferiority of conventionally fractionated intensity modulated radiation therapy with a simultaneous integrated boost to 3-dimensional conformal radiation therapy with a sequential boost for adjuvant breast radiation therapy. - Methods and Materials - A total of 502 patients were randomized between 2011 and 2015 for the prospective, multicenter, phase III trial (NCT 01322854). Five-year results of late toxicity (late effects normal tissue task force-subjective, objective, management, and analytical), overall survival, disease-free survival, distant disease-free survival, cosmesis (Harvard scale), and local control (noninferiority margin at hazard ratio [HR] of 3.5) were analyzed after a median follow-up of 62 months. - Results - The 5-year local control rate for the intensity modulated radiation therapy with simultaneous integrated boost arm was non-inferior to the control arm (98.7% vs 98.3%, respectively; HR, 0.582; 95% CI, 0.119-2.375; P = .4595). Furthermore, there was no significant difference in overall survival (97.1% vs 98.3%, respectively; HR, 1.235; 95% CI, 0.472-3.413; P = .6697), disease-free survival (95.8% vs 96.1%, respectively; HR, 1.130; 95% CI, 0.487-2.679; P = .7758), and distant disease-free survival (97.0% vs 97.8%, respectively; HR, 1.667; 95% CI, 0.575-5.434; P = .3601). After 5 years, late toxicity evaluation and cosmetic assessment further showed no significant differences between treatment arms. - Conclusions - The 5-year results of the IMRT-MC2 trial provide strong evidence that the application of conventionally fractionated simultaneous integrated boost irradiation for patients with breast cancer is both safe and effective, with noninferior local control compared with 3-dimensional conformal radiation therapy with sequential boost.
Gesehen am 19.03.2024